Hollow microspheres for gastroretentive floating- pulsatile drug delivery: preparation and in vitro evaluation - Maryam Maghsoodi; Elham Hemati; Bahram Qadermazi; Zahra Yari (Tabriz University of Medical Sciences, 2011)
Purpose: A multiparticular floating-pulsatile drug delivery system was developed for time and site specific drug release of piroxicam. A blend of floating and pulsatile principles of drug delivery system would have the advantage that a drug can be released in the upper GI tract after a definite time period. Methods: Hollow microspheres were prepared by the emulsion solvent diffusion method using Eudragit S as an enteric acrylic polymer with piroxicam at various polymer/drug ratios in a mixture of dichloromethane and ethanol. Developed formulations were evaluated for yield, encapsulation efficiency, particle size, shape, apparent density, buoyancy studies and dissolution studies. Results: The obtained microballoons were spherical with no major surface irregularity and mean particle size ranging from 250 to 380 for different batches. Formulations show a slight amount of relaese ranging from 0.7 to 11% in acidic medium (SGF) with complete release of drug in simulated intestinal fluid (SIF) in less than 3 h. Encapsulation efficiency of different formulations varied from 90 to 98%. The optimum loading amount of drug in the particles was found to impart suitable floatable properties to the microballoons. With increasing polymer/drug ratio, buancy of the microballoons increases accompanied by simultaneous reduction of apparent particle density. Conclusion: A pulsatile release of piroxicam was demonstrated by a simple drug delivery system which could be useful in chronopharmacotherapy of rheumatoid arthritis.